CHANG-ES XXIII: influence of a galactic wind in NGC 5775. Issue 1 (2nd October 2021) - Heald, G H; Heesen, V; Sridhar, S S; Beck, R; Bomans, D J; Brüggen, M; Chyży, K T; Damas-Segovia, A; Dettmar, R-J; English, J; Henriksen, R; Ideguchi, S; et al.
ABSTRACT: We present new radio continuum images of the edge-on starburst galaxy NGC 5775, from LOFAR (140 MHz) and the Karl G. Jansky Very Large Array CHANG-ES survey (1500 MHz). We trace the non-thermal radio halo up to 13 kpc from the disc, measuring the non-thermal spectral index and estimating the total equipartition magnetic field strength (≈13 μ G in the disc and ≈7 μ G above the plane). The radio halo has a similar extent at both frequencies, displays evidence for localized cosmic ray streaming coinciding with prominent H α filaments and vertical extensions of the regular magnetic field, and exhibits a boxy morphology especially at 140 MHz. In order to understand the nature of the disc–halo flow, we extend our previous model of cosmic ray propagation by implementing an iso-thermal wind with a tunable 'flux tube' (approximately hyperboloidal) geometry. This updated model is successful in matching the vertical distribution of non-thermal radio emission, and the vertical steepening of the associated spectral index, in a consistent conceptual framework with few free parameters. Our new model provides the opportunity to estimate the mass outflow driven by the star formation process, and we find an implied rate of M≈ 3 –6 M_ yr^-1 (≈40–80 per cent of the star formation rate) if the escape velocity is reached, with substantial uncertainty arising from the poorly understood distribution of interstellar medium material entrained in the vertical flow. The wind may play a role in influencing the vertical gradient in rotational velocity.